Advances in the development of entry inhibitors for sialic-acid-targeting viruses. Issue 1 (January 2021) - Heida, Rick; Bhide, Yoshita C.; Gasbarri, Matteo; Kocabiyik, Özgün; Stellacci, Francesco; Huckriede, Anke L.W.; Hinrichs, Wouter L.J.; Frijlink, Henderik W.
Highlights: Entry inhibitors might overcome the limitation of viral mutation. Antiviral research benefits from a broad-spectrum approach. Sialic acids can serve as a platform to create broad-spectrum antiviral drugs. Sialic-acid-targeting drugs such as DAS-181 are promising antiviral strategies. Multivalency is crucial when designing sialic-acid-based receptor analogues. Abstract : Over the past decades, several antiviral drugs have been developed to treat a range of infections. Yet the number of treatable viral infections is still limited, and resistance to current drug regimens is an ever-growing problem. Therefore, additional strategies are needed to provide a rapid cure for infected individuals. An interesting target for antiviral drugs is the process of viral attachment and entry into the cell. Although most viruses use distinct host receptors for attachment to the target cell, some viruses share receptors, of which sialic acids are a common example. This review aims to give an update on entry inhibitors for a range of sialic-acid-targeting viruses and provides insight into the prospects for those with broad-spectrum potential.